Managing a nosocomial outbreak of carbapenem‐resistant Klebsiella pneumoniae: an early Australian hospital experience. Issue 10 (October 2015) - Chang, L. W. K.; Buising, K. L.; Jeremiah, C. J.; Cronin, K.; Poy Lorenzo, Y. S.; Howden, B. P.; Kwong, J.; Cocks, J.; Blood, A.; Greenough, J.; Waters, M. J.
Abstract Background Carbapenems are traditionally reserved as the last line of defence for treatment of serious infections with multiresistant Gram‐negative bacilli. Reports of Klebsiella pneumoniae carbapenemase (KPC)‐producing organisms have been emerging globally, but rare in Australasia to date. We describe an outbreak of KPC‐2 producing K. pneumoniae at an Australian hospital. Methods After initial detection in October 2012, a retrospective review of patients with meropenem‐resistant K. pneumoniae to June 2012, and ongoing prospective surveillance, was undertaken. Included patients were admitted to the hospital after June 2012 and had meropenem‐resistant K. pneumoniae isolated from any site. Available isolates underwent detection of the KPC‐2 gene by polymerase chain reaction and molecular typing was performed to determine genetic relatedness between isolates. Point‐prevalence screening was performed on selected wards to detect asymptomatic carriage. Infection control procedures were implemented to contain the outbreak. Results Ten cases were identified in the initial cluster. Eight were localised to a single inpatient ward. Point‐prevalence screening revealed one extra case. After temporary containment, re‐emergence of KPC‐producing isolates was observed post October 2013 with 18 further cases identified. Four K. pneumoniae isolates in the 2012 cluster and 16 from the 2013–2014 cluster were referred for further testing. All carried the KPC‐2 beta‐lactamase gene. The 2012 isolates were genetically similar to the 2014 isolates. Conclusion KPC‐2 mediated resistance is an emerging threat in Australia. The re‐emergence of KPC despite initial containment emphasises the need for constant vigilance in the microbiology laboratory and ongoing maintenance of infection control and antimicrobial stewardship activity.